Indonesian Telemedicine: Between Hope and Legal Challenges - Syarifuddin, Andi (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The presence of telemedicine in the era of society 5.0 has revolutionized the development of equal distribution of information systems in the field of digital-based health. The research conducted is a literature review study with a descriptive analysis method. The approach used is a conceptual approach discussing telemedicine, prescriptive nature, and providing analysis and recommendations related to the need to develop more comprehensive regulations for telemedicine. Based on the results of the Telemedicine Service Policy in Indonesia, the digitalization project needs to be supported by a comprehensive legal and regulatory framework and see the importance of utilizing telemedicine in health services. And Legal Problems in Providing Remote Health Services Using Information and Communication Technology (Telemedicine) that important aspects in the health care system, such as the rights and obligations of the government to health service standards, the use of telemedicine services. Starting from patient privacy regulations. Based on the application, the hope is to improve telemedicine for people living in remote areas. Without clear and precise legal construction, the potential benefits of telemedicine are neglected. The solution is to develop regulations that are able to adapt and develop sustainably as telemedicine facilities and bring benefits.